2018
DOI: 10.1016/j.gpb.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The Immunome of Colon Cancer: Functional in Silico Analysis of Antigenic Proteins Deduced from IgG Microarray Profiling

Abstract: Characterization of the colon cancer immunome and its autoantibody signature from differentially-reactive antigens (DIRAGs) could provide insights into aberrant cellular mechanisms or enriched networks associated with diseases. The purpose of this study was to characterize the antibody profile of plasma samples from 32 colorectal cancer (CRC) patients and 32 controls using proteins isolated from 15,417 human cDNA expression clones on microarrays. 671 unique DIRAGs were identified and 632 were more highly react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 73 publications
2
15
0
Order By: Relevance
“…These proteins are essential for protein biosynthesis as well as RNA splicing and modification, cell growth, and proliferation, regulation of apoptosis and development of tumor cells [ 49 , 50 , 51 ] via signaling pathways usually altered in sCRC like Id-1/PI3K/Akt/NF-κB or p53 signaling pathway [ 49 , 51 , 52 ]. In accordance with our results, Coronell et al have recently defined the immunome of colon cancer employing protein microarrays that include aAbs against ribosomal proteins (RPS9 and RPL18) [ 53 ]. Additionally, Garranzo-Asensio et al recently reported a set of 31 proteins with altered expression at mRNA level in a serum characterization by protein microarrays [ 54 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These proteins are essential for protein biosynthesis as well as RNA splicing and modification, cell growth, and proliferation, regulation of apoptosis and development of tumor cells [ 49 , 50 , 51 ] via signaling pathways usually altered in sCRC like Id-1/PI3K/Akt/NF-κB or p53 signaling pathway [ 49 , 51 , 52 ]. In accordance with our results, Coronell et al have recently defined the immunome of colon cancer employing protein microarrays that include aAbs against ribosomal proteins (RPS9 and RPL18) [ 53 ]. Additionally, Garranzo-Asensio et al recently reported a set of 31 proteins with altered expression at mRNA level in a serum characterization by protein microarrays [ 54 ].…”
Section: Discussionsupporting
confidence: 90%
“…High expression levels of these proteins have been associated with cell invasion and metastasis in sCRC as well as adverse prognosis [ 24 , 25 , 60 ]. Alterations in the expression levels of these binding proteins might cause instability of the cellular structures and become auto-antigens in sCRC that have been detected in several studies [ 41 , 53 , 61 ]; in this line, Cha et al have identified 163 pairs of antibody peptides and possible antigenic peptides that belonged to aberrant proteins [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…5b), whose dysfunction tend to lead to tumorigenesis [29], metastasis [49], resistance [31], etc. With respect to wnt signaling, lost function of DDGs such as inhibitory SMAD4 and APC would definitely enhance the function of wnt signaling leading to tumorigenesis [5057], while attenuated function of ubiquitin mediated proteolysis facilitate proliferation [58]. Wherein, we found 10 highly concordant genes with a strong relation to patient overall survival including 5 AUGs and 1 DDG (Table 3), while FYTTD1 has been hardly reported to be associated with cancer.…”
Section: Discussionmentioning
confidence: 83%
“…Intratumoral bacterial colonization and residency, whether localized within myeloid cells or in tumor cells have recently been described to modulate local metabolism, change tumor cell biology or interfere in the drug catabolism ( 211 , 280 ). IgG responses directed against intratumoral bacteria may contribute to preventing tumor colonization and/or tumor killing, in both mouse models and patients ( 30 , 281 , 282 ).…”
Section: Towards a Solution To The Paradox Of Colon Cancersmentioning
confidence: 99%